Dampak Hukum Penghapusan Pasal 20 UU No. 13 Tahun 2016 tentang Paten (Legal Impact of Abolishing Article 20 of Law No. 13 of 2016 on Patent) - Trias Palupi Kurnianingrum (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2022)
The abolition of Article 20 of Law No. 13 of 2016 on Patent (Patent Law) related to the obligations of patent holders after the enactment of Law No. 11 of 2020 on Job Creation has caused debate. The debate is not without reason because removing the patent holder’s obligation to make products or use processes in Indonesia will indirectly reduce technology transfer, investment absorption, and/or employment. This article uses a normative juridical method to discuss the background of the abolition of Article 20 of the Patent Law and its legal consequences. In the discussion, it is stated that the background to the abolition of Article 20 of the Patent Law was influenced by several reasons, including flexibility in the obligation to make products or use processes in Indonesia, discrimination in Article 27 paragraph (1) of the TRIPS Agreement, violation of Article 20 of the Patent Law which resulted in the revocation of patents, and raw material difficulties. Removing Article 20 of the Patent Law is considered a non-solution because of the various legal consequences that arise from health and business aspects to the potential to create disharmony in the rules. It is necessary to revise the Patent Law to create legal certainty for patent holders who wish to register their patents or transfer their rights through licenses both in Indonesia and abroad. AbstrakPenghapusan Pasal 20 UU No. 13 Tahun 2016 tentang Paten (UU Paten) terkait kewajiban pemegang paten pasca diberlakukannya UU No. 11 Tahun 2020 tentang Cipta Kerja telah menimbulkan perdebatan. Hal ini bukannya tanpa sebab dikarenakan dengan menghapus kewajiban pemegang paten untuk membuat produk atau menggunakan proses di Indonesia secara tidak langsung akan menghilangkan transfer teknologi, penyerapan investasi dan/atau penyediaan lapangan kerja. Artikel ini menggunakan metode yuridis normatif membahas latar belakang penghapusan Pasal 20 UU Paten dan akibat hukum di dalamnya. Dalam pembahasan disebutkan bahwa latar belakang penghapusan Pasal 20 UU Paten dipengaruhi oleh beberapa sebab di antaranya: fleksibilitas kewajiban membuat produk atau menggunakan proses di Indonesia, diskriminasi Pasal 27 ayat (1) Perjanjian TRIPS, pelanggaran Pasal 20 UU Paten yang berakibat pada pencabutan paten, serta kesulitan bahan baku. Menghapus Pasal 20 UU Paten dianggap bukan merupakan solusidikarenakan beragamnya akibat hukum yang ditimbulkan mulai dari aspek kesehatan, bisnis, hingga berpotensi menciptakan ketidakharmonisan aturan. Diperlukan adanya revisi UU Paten guna menciptakan kepastian hukum bagi pemegang hak yang ingin mendaftarkan patennya atau yang ingin melakukan pengalihan hak melalui lisensi baik di Indonesia maupun di luar negeri.